Politik Hukum Presidential Threshold di Indonesia: Arah Pergeseran Konstitusional Pasca Putusan Mahkamah Konstitusi - Muhamad Iqbal Ansori Firdaus; Dian Hadiana (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
The debate over the presidential threshold in Indonesia’s constitutional system has persisted for years. However, most existing studies tend to focus either on its normative justification or its electoral consequences, without comprehensively situating the policy within the framework of legal politics and its constitutional implications following the Constitutional Court’s ruling. Addressing this research gap, this study aims to analyze the legal-political dynamics of the presidential threshold in Indonesia, tracing its development from its initial formulation to its eventual annulment by the Constitutional Court. This study employs a normative legal research method, utilizing statutory, conceptual, and analytical approaches. The research is based on an examination of primary, secondary, and tertiary legal materials, which are qualitatively analyzed to assess the policy’s underlying rationale and its compatibility with constitutional principles. The findings reveal that the presidential threshold was originally designed as an instrument to simplify presidential nominations and promote governmental stability. However, in practice, it has instead narrowed political representation, strengthened party oligarchy, and intensified political polarization. The study further demonstrates that governmental stability in Indonesia has been shaped more by post-election negotiations and the practice of presidential coalition-building than by the threshold mechanism itself. The Constitutional Court’s decision to invalidate Article 222 of the Election Law signifies a fundamental shift in the design of presidential candidacy, affirming that the presidential threshold is incompatible with the principles of popular sovereignty, proportionality, and political equality. The implications of this study underscore the need to restructure the presidential nomination system in a more inclusive and constitutionally grounded manner, while encouraging electoral law reforms that prioritize substantive democratic values over formal stability considerations.